Second Scholasticism and Black Slavery1 (Continuation and End) - Pich, Roberto Hofmeister (Veritas (Porto Alegre), 2020)
In order to systematically explore the normative treatment of black slavery by Second Scholastic thinkers, who usually place the problem within the broad discussion of moral conscience and, more narrowly, the nature and justice of trade and contracts, I propose two stations of research that may be helpful for future studies, especially concerning the study of Scholastic ideas in colonial Latin America. Beginning with the analysis of just titles for slavery and slavery trade proposed by Luis de Molina S.J. (1535–1600), I show how his accounts were critically reviewed by Diego de Avendaño S.J. (1594–1688), revealing basic features of Second Scholasticism’s normative thinking in Europe and the Americas. The normative knowledge provided by these two Scholastic intellectuals would be profoundly tested during the last decades of the 17th century, especially by authors who sharpened the systemic analysis and a rigorist moral assessment of every title of slavery and slaveholding, as well as the requirements of an ethics of restitution.